A case series of pediatric survivors of anaplastic pleomorphic xanthoastrocytoma. Issue 1 (30th January 2021) - Ronsley, Rebecca; Dunham, Christopher; Yip, Stephen; Brown, Lindsay; Zuccato, Jeffrey A; Karimi, Shirin; Zadeh, Gelareh; Goddard, Karen; Singhal, Ash; Hukin, Juliette; Cheng, Sylvia
Abstract: Background: Anaplastic pleomorphic xanthoastrocytoma (APXA) is a rare subtype of CNS astrocytoma. They are generally treated as high-grade gliomas; however, uncertainty exists regarding the optimal therapy. Here, we report on 3 pediatric cases of APXA. Methods: Our institutional database was queried for cases of APXA and 3 cases were identified. Surgical samples were processed for methylation profiling and chromosomal microarray analysis. Methylation data were uploaded to the online CNS tumor classifier to determine methylation-based diagnoses to determine copy number variations (CNVs). Results: Two patients were male, 1 female, and all were aged 12 years at diagnosis. All underwent a gross total resection (GTR) and were diagnosed with an APXA. Immunohistochemical analysis demonstrated that 2 cases were BRAF V600E positive. Methylation-based tumor classification supported the APXA diagnosis in all cases. CNV analyses revealed homozygous CKDN2A deletions in all and chromosome 9p loss in 2 cases. All patients received radiation therapy (54 Gy in 30 fractions) with concurrent temozolomide. Two patients received maintenance chemotherapy with temozolomide and lomustine for 6 cycles as per the Children's Oncology Group ACNS0423. The third patient recurred and went on to receive a second GTR and 6 cycles of lomustine, vincristine, and procarbazine. All are alive with no evidence of disease >4 years post-treatment completion (overall survival = 100%, event free survival = 67%). Conclusions: The natural history and optimal treatment of this rare pediatric tumor are not well understood. This case series supports the use of adjuvant chemoradiotherapy in the treatment of APXA. The genetic landscape may be informative for optimizing treatment and prognosis.